Timely diagnosis of emphysematous pyelitis by point-of-care ultrasound in an outpatient setting prevented infection spread: a case report and review of the literature - Octavio J. Salgado; Angela M. Vidal; Abhilash Koratala; Zoila K. Salazar-Torres; Hermel M. Espinosa (Journal of Medical Case Reports)
Abstract Background Emphysematous pyelitis represents the initial stage of emphysematous pyelonephritis, a rare and potentially life-threatening necrotizing renal infection caused by gas-forming bacteria. Diabetes mellitus and/or lithiasis constitute significant risk factors for such conditions. Renal point-of-care ultrasound is an invaluable diagnostic tool for the early detection of gas within the kidney and urinary tract. The present case provides an illustrative example of the crucial importance of routinely using renal point-of-care ultrasound in every patient with a suspected urinary tract infection in an outpatient setting. Case presentation A 55 year-old hypertensive, non-diabetic female patient of Wayuu indigenous ethnicity was evaluated for mild-to-moderate right flank pain accompanied by slight fever at night. She was referred to the renal outpatient clinic with a presumptive urinary tract infection. In the context of a systemic review for symptoms, the patient reports expulsion of gas bubbles during urination. She was evaluated by ultrasound, which detected gas in the pyelocaliceal system. A computed tomography scan confirmed this. The patient was admitted to the hospital and started on intravenous therapy with ceftriaxone. Urine culture revealed the presence of E. coli > 100 CFU sensitive to ceftriaxone. The response to antibiotherapy was favorable, with remission of clinical symptoms and moderate leukocytosis observed at the time of admission. Conclusion Routine point-of-care ultrasound evaluation should be part of the physical evaluation of every patient presenting with a suspected upper urinary tract infection in the renal outpatient clinic.